Wind farm layout design using cuckoo search algorithm - Rehman, S. (SciTePress, 2016)
Wind energy has emerged as a strong alternative to fossil fuels for power generation. To generate this energy, wind turbines are placed in a wind farm. The extraction of maximum energy from these wind farms demands an efficient layout of the wind farms. This layout determines the location of each turbine in the wind farm. Due to its sheer complexity, the wind farm layout design problem is considered a complex optimization problem. In recent years, several attempts have been made to develop techniques and algorithms for optimization of wind farms. This paper proposes yet another optimization algorithm based on the cuckoo search (CS), which is a recent optimization method. The proposed cuckoo search algorithm is compared with genetic algorithm which is by far the highest utilized algorithm for wind farm layout design. Empirical results indicate that the proposed cuckoo search algorithm outperformed the genetic algorithm for the given test scenarios in terms of yearly power output and efficiency. Â© Copyright 2016 by SCITEPRESS - Science and Technology Publications, Lda. All rights reserved.